Peran Human Capital Dalam Peningkatan Kualitas Sumber Daya Manusia Di Rumah Sakit - Wahyuni, Sri; Nurfarahin, Nurfarahin; Vidian, Anggy; Hartono, Budi (JURNAL PENDIDIKAN KESEHATAN, 2024)
Human capital plays a strategic role in the management of human resources (HR) in hospitals, which in turn affects the quality of health services provided. This article aims to evaluate the role of human capital in improving the quality of hospital human resources through the management of employee skills, knowledge, and competencies. This research emphasizes the importance of training, career development, and technology integration as a tool for human resource development. A literature review shows that effective human capital management is able to improve employee performance and service efficiency. However, challenges in terms of training budget constraints, management support, and technology adoption are the main obstacles that must be overcome. Keywords: Human Capital, Human Resources development, hospitals, employee management